2016
DOI: 10.1021/acs.jpcc.5b06680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Assembled Monolayers on the Locally Electrodeposited Silver Thin Layers

Abstract: The localized electrodeposition of silver on gold coated with self-assembled monolayers (SAMs) by scanning electrochemical microscopy (SECM) is reported. The SAMs were ω-functionalized alkanethiols of the form X−(CH 2 ) 2 SH, X = OH, NH 2 , CO 2 H, SO 3 H, as well as 4-mercaptobenzoic acid. The SAMs were characterized by X-ray photoelectron spectroscopy (XPS) and cycling voltammetry (CV). The anodic dissolution of a Ag microelectrode, which was held within a few microns from the Au surface, formed a well-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This suggests enormous potential of the functional SAMs for clinical applications. The physical adsorption, covalent and covalent coordinate bond methods have been developed for molecules immobilization onto SAM [16,17], such as covalent immobilization of proteins [18]. Among the intermolecular interactions developed for molecules immobilization on SAM, those based on weak interactions still need to explore [19].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests enormous potential of the functional SAMs for clinical applications. The physical adsorption, covalent and covalent coordinate bond methods have been developed for molecules immobilization onto SAM [16,17], such as covalent immobilization of proteins [18]. Among the intermolecular interactions developed for molecules immobilization on SAM, those based on weak interactions still need to explore [19].…”
Section: Introductionmentioning
confidence: 99%
“…Metallic nanoparticles (NPs) are commonly prepared in solution. , Yet, it is possible to form metallic NPs directly on surfaces. The latter is of special importance in a variety of fields, such as (electro)­catalysis, sensing, energy, etc. , In growing NPs on either conducting or nonconducting surfaces, the particle–surface interaction plays a major role. , Furthermore, one of the reasons for growing NPs directly on surfaces is to control their location and density for further applications, e.g., catalysis. , Key factors affecting the growth and properties of the NPs at the solid–liquid interface comprise the nature of the NPs and the surface (including surface defects) and their crystallinity . Numerous synthetic approaches for the formation of metallic NP arrays on different surfaces have been reported. , They can be divided into parallel and serial methods.…”
Section: Introductionmentioning
confidence: 99%
“…Others and we have shown the applicability of SECM as a patterning tool for the local deposition, etching, polymerization, and additional chemical and electrochemical reactions . Recently, we have shown that SECM enables controlling the crystal growth of metal NPs deposited locally on conducting surfaces. ,, We have demonstrated two approaches of controlling the growth of NPs locally on conducting surfaces (Scheme ). The surfactant-based method (Scheme A) involves the addition of shape affecting agents to the solution and generating a flux of metallic ions that are electrochemically reduced on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electrochemical microscopy (SECM), a scanning probe technique with high spatial resolution was evolved as a means of imaging, studying interfacial processes or modifying surfaces. [14][15][16][17] Indeed, SECM has been used to form metallic patterns of Au, [18][19][20][21] Ag, [22] Co [23] and other metals on various surfaces using different modes, e. g. feedback and generation/ collection. [24] Other approaches, including scanning probe microscopy, [25] chemical etching, [26] laser irradiation [27] and electrochemistry using masks [28] have been reported to achieve micrometer resolution through local deposition followed by electroless metal deposition on different substrates.…”
Section: Introductionmentioning
confidence: 99%